Benchmarking and entrepreneurs' activities in the area of good CSR practices in the field of work - Ewa Stawicka (Uniwersytet Kazimierza Wielkiego, 2019)
The aim of the study is to present benchmarking as an element of management towards the implementation of social responsibility in an organization. The concept of benchmarking is created on the basis of best practice models implemented in management processes. The issue of benchmarking was presented in terms of theory and practices of social responsibility in Poland in terms of ISO 26000 standard in practical terms. The data from the Good Practice Reports prepared by the Responsible Business Forum were analysed. The data indicate that year by year there are more and more examples of good practices in all areas according to the ISO 26000 standard. Particular attention was paid to the growing number of solutions in the field of work, as a result of benchmarking. It was found that in the years 2008-2018 within the framework of mutual benchmarking of companies, the number of good practices in the field of work increased from 16 to 237 practices. Benchmarking of good practices in the field of work is also a confirmation of the implementation of trends contained in the Objectives of Sustainable Development, especially Objective 3, 8 and 4. The article is a contribution to a detailed analysis of what type, course and scheme of the benchmarking process occurs most frequently in Polish organizations and what is the effectiveness of the phenomenon.